Suppression of Rat Oral Carcinogenesis by Agonists of Peroxisome Proliferator Activated Receptor γ. - David L McCormick; Thomas L Horn; William D Johnson; Xinjian Peng; Ronald A Lubet; Vernon E Steele (PLoS ONE)
Peroxisome-proliferator-activated receptor γ (PPARγ) is a ligand-activated transcription factor that regulates cell proliferation, differentiation, and apoptosis. In vivo studies were performed to evaluate the activities of two thiazolidinedione PPARγ agonists, rosiglitazone and pioglitazone, as inhibitors of oral carcinogenesis in rats. Oral squamous cell carcinomas (OSCC) were induced in male F344 rats by 4-nitroquinoline-1-oxide (NQO; 20 ppm in the drinking water for 10 weeks). In each study, groups of 30 NQO-treated rats were exposed to a PPARγ agonist beginning at week 10 (one day after completion of NQO administration) or at week 17 (7 weeks post-NQO); chemopreventive agent exposure was continued until study termination at week 22 (rosiglitazone study) or week 24 (pioglitazone study). Administration of rosiglitazone (800 mg/kg diet) beginning at week 10 increased survival, reduced oral cancer incidence, and reduced oral cancer invasion score in comparison to dietary controls; however, chemopreventive activity was largely lost when rosiglitazone administration was delayed until week 17. Administration of pioglitazone (500 mg/kg diet beginning at week 10 or 1000 mg/kg diet beginning at week 17) induced significant reductions in oral cancer incidence without significant effects on OSCC invasion scores. Transcript levels of PPARγ and its three transcriptional variants (PPARγv1, PPARγv2, and PPARγv3) were not significantly different in OSCC versus age- and site-matched phenotypically normal oral tissues from rats treated with NQO. These data suggest that PPARγ provides a useful molecular target for oral cancer chemoprevention, and that overexpression of PPARγ at the transcriptional level in neoplastic lesions is not essential for chemopreventive efficacy.